Germinação, desenvolvimento inicial, fenologia e distribuição espacial da espécie Dalbergia cearensis Ducke - Nogueira, Francisco Carlos Barboza (2012)
The viable seed production, dispersal, germination and early growth of seedlings are events of the life cycle of angiosperms that are part of the regeneration niche. Understanding how these events occur before environmental factors such as temperature, light and humidity and how the young and adult individuals are spatially distributed in the environment, increases the probability of getting success in the establishment of plant species and their future growth. Dalbergia cearensis is an endemic species of xerophilous thorny forest (caatinga) of northeastern Brazil. Its wood is much appreciated for the production of finely crafted furniture and musical instruments. In this study, we tried to understand the morphology of its fruit, seeds, and seedlings, the influence of light and temperature on seed germination, phenology, and spatial distribution. Fruits of D. cearensis were described as samaras which have features to spread anemochorous dispersion. Its germination process is relatively fast, beginning after three days of sowing. Its seeds germinate in the presence and absence of light, with the highest percentage of germination reached at temperatures of 25, 30 and 35oC. The young plants of D. cearensis show greater shoot growth under shade and their roots grow in the full light. Your tree loses leaves during the dry season which runs from July to December. At the beginning of rains (December), it starts the issuance of leaf buds which happens until March. Its flowers appear with the rain constancy and can happen between November and January. The phenological peak of ripi fruit happens in May. The young and adult population placed in Private Reserve of Natural Patrimony Não Me Deixes Farm in Quixadá, Ceará shows aggregated distribution. The highest proportion of seeds dispersed is 3 meters away from the nearest adult.